Corruption and optimal regulation under common agency - Pedro Hemsley (EconomiA, 2016)
I show that it is optimal to separate non-benevolent regulators when regulated projects are large. Separation prevents regulators from coordinating to appropriate all of the agent's informational rent when they know the type of the latter; therefore, there is a trade-off between saving on informational rent and efficiency, since the game between the regulators induced by separation causes further distortions when compared to the allocation under one regulator. When the informational rent at stake is large due to the size of the project, separation is the optimal institutional answer. – – Mostro que separar reguladores n\~ao-benevolentes é a resposta institucional ótima quando os projetos regulados s\~ao grandes. Como separaç\~ao impede que os reguladores se coordenem para se apropriar de toda a renda informacional do agente quando sabem o tipo desse último, há um trade-off entre poupança de renda informacional e eficiência alocativa, pois o jogo entre os reguladores induzido pela separaç\~ao gera distorç\~ao em relaç\~ao à alocaç\~ao com um único regulador. Quando a renda informacional em quest\~ao é grande, vale a pena a divis\~ao de reguladores.
Keywords: D73; D78; D82; D8; 330; Regulation; Contract theory; Corruption